Analisis Faktot-Faktor Yang Mempengaruhi Nilai Perusahaan Dengan Kebijakan Deviden Sebagai Variabel Moderasi - Ichda Apriliana Lutfi; Fetria Eka Yudiana (el-Jizya: Jurnal Ekonomi Islam, 2021)
The research objectives are 1) to determine the effect of profitability, leverage, liquidity and dividend policy on firm value, 2) to determine the effect of dividend policy as a moderating variable in the relationship between profitability, leverage and liquidity on firm value. The type of research used in this study is quantitative with the population used are companies listed on the Jakarta Islamic Index for the period 2013-2019. The sampling technique used purposive sampling method, so that a sample of 13 companies registered in the Jakarta Islamic Index for the 2013-2019 period was obtained. The data analysis technique used in this research is Moderated Regression Analysis and hypothesis testing using eviews. Based on the results of hypothesis testing shows that: 1) profitability has a positive and significant effect on firm value. 2) Leverage has a negative and significant effect on firm value. 3) Liquidity has a negative and significant effect on firm value. 4) Dividend policy has a negative and significant effect on firm value. 5) Dividend policy weakens the relationship between profitability and firm value. 6) Dividend policy strengthens the relationship of leverage to firm value. 7) Dividend policy strengthens the relationship between liquidity and firm value.